2003
DOI: 10.1002/art.11297
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between birth order and juvenile idiopathic arthritis

Abstract: Lack of association between birth order and juvenile idiopathic arthritisAlthough the cause of juvenile idiopathic arthritis (JIA) is still not well elucidated, evidence suggests that a complex interplay of genetic and environmental factors underlies its pathogenesis. JIA includes phenotypically and genetically distinct subtypes, with different ages at onset. It has been hypothesized that intrauterine or early childhood environmental factors might influence susceptibility to autoimmune diseases. It is conceiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Our data are consistent with this finding, showing that risk of JIA in only children is 2.2 times higher than that in children with at least one sibling. Prahalad et al showed no association between birth order and JIA (15). Again, our data are consistent with this work.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data are consistent with this finding, showing that risk of JIA in only children is 2.2 times higher than that in children with at least one sibling. Prahalad et al showed no association between birth order and JIA (15). Again, our data are consistent with this work.…”
Section: Discussionsupporting
confidence: 93%
“…One study showed that an only child had a risk of developing “juvenile chronic arthritis” that was 1.6 times that of a child with at least one sibling . Another study revealed no relationship between juvenile arthritis and either birth order or sibship size (total number of children in the family) by comparison of 333 cases of “juvenile rheumatoid arthritis” and more than 3,000 controls matched to cases by age and sex . More recently, an analysis of more than 3,000 Swedish JIA cases and 13,000 controls did not find an association of JIA with number of older siblings .…”
mentioning
confidence: 98%
“…In contrast, no risk reduction was observed in relation to having increased numbers of older siblings in a Swedish registry-based study [5]. Birth order was not found to be associated with JIA in two previous studies [6, 20]. …”
Section: Discussionmentioning
confidence: 95%
“…This was also supported by a Norwegian study, which reported that singleton children had 1.6‐fold higher risk of JIA as compared to children with siblings. However, not all studies have observed the protective effect of contact with siblings …”
Section: Early Life Events and Jia Riskmentioning
confidence: 98%
“…However, not all studies have observed the protective effect of contact with siblings. 15,64 A final factor which is linked to microbial alteration is prematurity. In a Northern American study that included fecal samples obtained from 30 premature and 176 term infants at 6 weeks of age 65 reduced alpha diversity was found in preterm vs term infants even after adjusting for exposures.…”
Section: Other Environmental Factors Affecting Microbiota Colonizationmentioning
confidence: 99%